The origins of Christendom in the West - Kreider, Alan, 1941- (Edinburgh ; New York : T&T Clark, 2001)
For well over a millennium the civilization of Western Europe was 'Christendom, ' with Christianity the dominant religion, buttressed by social and legal structures. This volume studies Christendom at its origins, bringing the insights of leading scholars in the fields of ancient history, theology, patristics, and liturgy to bear on aspects of Europe's Christianization. From a missiological perspective, the contributors ask what is Christianity's impact upon culture, what is culture's impact upon Christianity? Focusing on the first four centuries, but also looking forward to the future of Chris.
Changing Patterns of Conversion in the West / Alan Kreider -- Christianization and Conversion in Northern Italy / Rita Lizzi Testa -- Christianity Shaped through its Mission / Ramsay MacMullen -- The Sociology of Pre-Constantine Christianity: Approach from the Visible / Wolfgang Wischmeyer -- Early Christian Features Preserved in Western Monasticism / Eoin de Bhaldraithe, OCist. -- Charism and Office in a Changing Church / Christine Trevett -- Women in the Christianization of the West / Anne Jensen -- Catechesis and Initiation / Everett Ferguson -- The Effects of the Coming of Christendom on Early Christian Worship / Paul F. Bradshaw -- Augustine and the Transformation of Baptism / David F. Wright -- Defining Heresy / Rowan Williams -- Comparative Inculturations / Antonie Wessels -- Epilogue: Approaching Christendom / Kate Cooper.
Includes bibliographical references and index.
ACU copy gift of Everett Ferguson.
Keywords: Church history -- Primitive and early church, ca. 30-600.; Povijest crkve -- Rano kršćanstvo, ca. 30-600.; Christianity -- Europe; Kršćanstvo -- Europa